Novel multi-target therapeutic potential of the genus Inula: Advances and opportunities for neuroprotection - Marjan Talebi; Mona Khoramjouy; Afsoon Feizi; Zulfıqar Ali; Ikhlas A. Khan; Neda Alsadat Ayatollahi; Seyed Abdulmajid Ayatollahi; Mehrdad Faizi (Elsevier, 2023)
Ethnopharmacological relevance: The important genus Inula contains more than 100 species and is widespread in the temperate regions of Asia, Africa, and Europe. Numerous Inula species have an ethnobotanical background and are used in Traditional Chinese Medicine (TCM). Aim of the study: This review is a comprehensive study of the more practical therapeutic uses of Inula spp. and their phytochemical compounds in terms of their pharmacological activities, mainly neuroprotective effects. Traditional uses of the genus are described by focusing of TCM. Pharmaceutical, cosmeceutical, and ecological impacts, and their importance in food science, are elaborated upon as well. The pharmacokinetic profile, safety, and toxicity of this genus are also described. Materials and methods: Literature in this review was searched in PubMed, Scopus, Web of Science, and Google Scholar using the keywords "Inula", "neuro*", "Alzheimer's disease", "neuroinflammation", "seizure", "epilepsy", "headache", "nociception", "pain", "insomnia", "neurotoxicity", "depression", "glioblastoma", and "traumatic brain injury". Results: This study will provide insight into the neuropharmacological applications of Inula spp. by focusing on the attributed mechanisms of action. The genus Inula has promising protective effects against Alzheimer's disease, neuroinflammation, seizures, insomnia, headaches, neurotoxicity attributed to oxidative damage, depression, nociception, traumatic brain injury, neuromuscular dysfunction, glioblastoma, and primary amoebic meningoencephalitis by targeting various mechanisms and signaling pathways. Conclusion: Due to the acceptable oral bioavailability, blood-brain barrier permeability, and low toxicity of Inula spp. they can be considered promising alternative neuroprotective agents. However more clinical studies are needed in this regard.